HOLISTIC TEACHING AND LEARNING APPROACH IN DAYCARE: AN ANALYSIS OF CURRENT PARENTS’ ASPIRATIONS AND NEEDS IN MALAYSIA - NUR AINA SYAFIEQA RAZALI; MOHD NAZRI ABDUL RAHMAN (P3I UMSurabaya, 2025)
This study discusses the implementation of teaching and learning approaches for infants and toddlers in TASKA that meet the aspirations of parents today. Through library research methods, this study examinedvarious scholarly sources, government reports and early childhood education policies in Malaysia. Theresults of the analysis found that the implementation of teaching and learning in TASKA plays animportant role in shaping the overall development of infants and toddlers in shaping the overalldevelopment of infants and toddlers in terms of cognitive, social, emotional and physical. Parents'aspirations now emphasize development-based education, safety, the value of love, and fun learning. Thestudy also discusses the challenges in implementing teaching and learning approaches andrecommendations to strengthen the country's early education in line with the National Early ChildhoodEducation Policy (DPAKK) and the National PERMATA Curriculum (KPN).